Impact of Smoking on Disease Severity and Mortality of Hospitalized Patients with Confirmed COVID-19 - Güllü, Yusuf Taha; Kulucan, Ebru; Tibel Tuna, Nazmiye; Köksal, Nurhan; Koca, Nizameddin (Addicta: The Turkish Journal on Addictions, 2022)
COVID-19 is a newly defined pandemic agent. Exposure to cigarette smoke causes increased mucosal inflammation, expression of inflammatory cytokines, impaired mucociliary clearance, and excessive mucus production. Changes in the lungs due to smoking can directly affect the outcome of the disease. In this study, we evaluated the relationship between smoking and the clinical severity of COVID-19. The charts of the patients with positive real-time polymerase chain reaction (RT-PCR) tests who received inpatient treatment in COVID-19 clinics between November 2020-April 2021 were reviewed retrospectively. Patients were divided into two groups smokers and non-smokers. We compared two groups’ age, gender, laboratory parameters, mortality status, and disease severity. We included PCR proven 165 smokers and 351 non-smokers who needed hospitalization. The number of female patients was significantly lower in the smoker group (F/M: 33/132)(p
Keywords: COVID-19; smoking; disease severity; mortality; mechanical ventilator